The Effect Of Advertising Promotions and Product Reviews On Online Purchase Decisions in E-Commerce - Wilma Elviana Sibarani (Outline Publisher, 2022)
This study aims to determine whether or not there is an effect of advertising promotions and product reviews on online purchasing decisions in e-commerce for students of the 2018 Stambuk Business Education Study Program, Medan State University. The population in this study were 53 students. The data collection technique in this study was carried out by distributing a questionnaire (questionnaire) whose measurements were carried out using a Likert scale and statistically processed. The data analysis technique used was classical assumption test, multiple linear regression analysis, determination calculation, and hypothesis testing. The results of data analysis using multiple linear regression and hypothesis testing can be concluded that partially the Advertising Promotion variable has no effect on purchasing decisions, then for the Product Reviews variable partially influence on purchasing decisions. Simultaneously there are influence with > 11.111 > 3.18) and significance value (0.000 < 0.05). With the magnitude of the influence of the two independent variables.